Predicting Sleep Quality Based on Migraine Headaches and Rumination in Women with Panic Attacks - Sarem, Arezoo; Valie, Simin; Sorkhabi abdolmalek, Mahvash; Pazoki, Shahrzad; Alimardani, Soroush (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to predict sleep quality based on migraine headaches and rumination in women with panic attacks. Methods: This applied and descriptive-correlational study included a sample of women who visited psychological clinics in the city of Isfahan. Using convenience sampling, 210 participants were selected. Data were collected using the Pittsburgh Sleep Quality Index (1989), Ahvaz Migraine Headache Symptoms Questionnaire (1997), and the Rumination-Reflection Questionnaire by Trapnell and Campbell (1999). For data analysis, simultaneous multiple regression was performed using SPSS version 21. Findings: The findings indicated that migraine headaches and rumination could explain 30.5% of the variance in sleep quality among patients with panic attacks. Specifically, with each standard deviation increase in migraine headache and rumination scores, there was a corresponding increase of 0.532 and 0.371 standard deviations in sleep quality scores, respectively (P < 0.01). Conclusion: Based on the results, migraine headaches and rumination can predict sleep quality in patients with panic attacks.